Pengembangan E-Modul Berbasis Pendekatan Contextual Teaching And Learning Pada Materi Barisan Dan Deret Untuk Meningkatkan Minat Belajar Siswa SMP - Martin Martin; Syamsuri Syamsuri; Heni Pujiastuti; Aan Hendrayana (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
This study aims to produce e-modules with a contextual teaching and learning approach that is valid, practical, and effective to increase students' interest in learning. This development research uses the Plomp model which consists of three phases, namely the preliminary research phase, the prototyping phase, and the assessment phase. The prototype trial was conducted on 16 eighth grade students of SMPN 1 Tirtayasa, Indonesia. The research instrument consisted of an expert validation sheet to assess the validity, a student response questionnaire to assess practicality, and a student learning interest questionnaire to assess the effectiveness of the e-module. This research produces an e-module with a contextual teaching and learning approach to increase the interest of junior high school students in learning mathematics in the context of everyday life. Although the increase in student interest in learning is still relatively low, overall the e-modules developed are considered valid, practical, and effective, so that they are suitable for use in learning mathematics in junior high schoolsKeywords: Mathematics Module, Contextual Teaching and Learning Interest in Learning Mathematics